An Engineered RNase P Ribozyme Effectively Reduces Human Coronavirus 229E Gene Expression and Growth in Human Cells - Yujun Liu; Bin Yan; Hao Gong; Fenyong Liu (Zoonotic Diseases)
The human coronavirus 229E (HCoV-229E) is a member of the human coronavirus family that includes SARS-CoV-2, the causative agent of COVID-19. Developing antiviral strategies and compounds is crucial to treat and prevent HCoV-229E infections and the associated diseases. Ribozymes derived from ribonuclease P (RNase P) catalytic RNA represent a novel class of promising gene-targeting agents by cleaving their target mRNA and knocking down the expression of the target mRNA. However, it has not been reported whether RNase P ribozymes block the infection and replication of HCoV-229E. We report here the engineering of an anti-HCoV-229E RNase P ribozyme to target an overlapping region of viral genomic RNA and the mRNA encoding the nucleocapsid (N) protein, which is vital for viral replication and growth. The engineered ribozyme actively hydrolyzed the viral RNA target in vitro. HCoV-229E-infected cells expressing the engineered, catalytically active ribozyme exhibited a reduction of about 85% in viral RNA levels and N protein expression, and a reduction of about 750-fold in infectious particle production, compared to cells expressing no ribozymes or a control, catalytically inactive ribozyme. Our study provides the first direct evidence of the therapeutic potential of RNase P ribozymes against human coronaviruses such as HCoV-229E.